Gambaran Penggunaan Obat Antiinflamasi Non Steroid Pada Pasien Penderita Osteoarthritis di Instalasi Rawat Jalan RSUD Kajen Periode Januari – Oktober 2024 - Isyna Hida; Rismi Fatoni (An-Najat, 2025)
Basic Health Research data in 2018 recorded that the rate of osteoarthritis sufferers in Central Java was around 6.78% and the rate of osteoarthritis sufferers in Pekalongan Regency was around 5.37%. Treatment of osteoarthritis can be done pharmacologically by administering non-steroidal anti-inflammatory drugs. The purpose of this study is to find out the description of the use of non-steroidal anti-inflammatory drugs in patients with osteoarthritis in the outpatient unit of Kajen Hospital, Pekalongan Regency. This type of research is non-experimental using a descriptive design with a quantitative approach and retrospective data collection using medical record data. The inclusion criteria in this study are patients with osteoarthritis in the outpatient unit of Kajen Hospital during January-October 2024 diagnosed with or without comorbidities. The data collection technique is purposive sampling. This study was conducted on 300 patients who met the inclusion criteria with the most characteristic results experienced by osteoarthritis patients aged 55-64 years, 45.00% were female, 74.64% were diagnosed with comorbidities, 93.00%. The most widely used non-steroidal anti-inflammatory drugs in the treatment of osteoarthritis in the outpatient installation of Kajen Hospital are Meloxicam 15 mg 48.67% and the most widely used non-steroidal anti-inflammatory drugs are COX-2 Selective Agents 89.67%.